2009
DOI: 10.7150/ijbs.5.265
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthitis of Leptin-Deficient ob/ob Mice in Response to Biomechanical Loading in Micro-CT

Abstract: Objective: Mechanotransduction is the mechanism that due to reacting chondrocytes on biomechanical loading of body mass. Higher biomechanical loading lead to increased degeneration of chondrocytes, whereas moderate loading is protecting. This suggests that body fat regulates bone metabolism first by means of hormonal factors and second that the effects of muscle and loading are signaling factors in mechanotransduction. Leptin, a peptide hormone produced predominantly by white fat cells, is one of these hormona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
5
0
2
Order By: Relevance
“…It is possible that the reduced variance explained in Modified Mankin Score by body fat in our study is due to the confounding effect of ACL-X. Others have shown that leptin deficient mice gained weight but did not develop OA 39,40 , which suggests that mass increase in the absence of leptin signaling is not sufficient to cause OA. In humans, the ratio of plasma leptin and synovial fluid leptin may be a marker of OA severity 41 .…”
Section: Table Imentioning
confidence: 70%
“…It is possible that the reduced variance explained in Modified Mankin Score by body fat in our study is due to the confounding effect of ACL-X. Others have shown that leptin deficient mice gained weight but did not develop OA 39,40 , which suggests that mass increase in the absence of leptin signaling is not sufficient to cause OA. In humans, the ratio of plasma leptin and synovial fluid leptin may be a marker of OA severity 41 .…”
Section: Table Imentioning
confidence: 70%
“…Osteoarthritis (OA) is a prevalent progressive and degenerative joint disease that results in personal activity limitations, disability, and great economic burden worldwide 1 . Various factors contribute to the initiation and progression of OA, such as age, gender, body weight, heredity, and mechanical injury 2 , 3 . The main treatment for OA has been to delay its development; few anti-inflammatory therapies have been used to relieve the symptoms of OA.…”
Section: Introductionmentioning
confidence: 99%
“…A high fat diet accelerates the onset of both obesity and OA in the C57BL/6J mouse strain 32 . Recent studies by Griffin et al and Heep et al show that C57BL mice develop OA in a leptin-dependent manner, associated with the degree of weight change 33,34 . Diet-induced OA in these genetically predisposed mice mimics both biomechanical and neurobehavioral mechanisms of OA e mice develop altered loading and associated pain 34 .…”
Section: Discussionmentioning
confidence: 99%